2023
DOI: 10.3390/chemengineering7040069
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Cold-Pressed Extraction of Sacha Inchi Seeds: Oil Yield and Its Physicochemical Properties

Sela Kong,
Tongor Keang,
Monyneath Bunthan
et al.

Abstract: Sacha inchi oil (SIO) extraction has been extensively studied using various oil extraction techniques to achieve a high oil recovery. However, most studies relied on heat-based methods, which led to compromised oil quality and reduced nutritional values, particularly polyunsaturated fatty acids (omega-3 and omega-6), vitamin E, and phenolic compounds. To address these concerns, this study employed a hydraulic cold-pressed extraction (HCPE) technique for extracting SIO aiming to enhance oil yield while preservi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Figure 1b shows that the mass of added bleaching earth is crucial in determining the effectiveness of color change in the CIE-Lab method, which is further confirmed by the work of Marrakchi et al [40] Doses of 2.5% by mass of BE5, BE6, and BE7 showed little ability to change the color of the tested oils (gray field in Figure 1b), but doses of 5.0% showed the greatest effectiveness in this matter (blue field in Figure 1b). Kong et al [41] showed that slight changes in the oil color determined by the CIE-Lab method occurred during repeated oil filtration. Referring to the conducted research, it can be concluded that some BEs in small doses (i.e., BE7; 2.5%, Finola CP) do not show the proper adsorption capacity to carotenoid dyes.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1b shows that the mass of added bleaching earth is crucial in determining the effectiveness of color change in the CIE-Lab method, which is further confirmed by the work of Marrakchi et al [40] Doses of 2.5% by mass of BE5, BE6, and BE7 showed little ability to change the color of the tested oils (gray field in Figure 1b), but doses of 5.0% showed the greatest effectiveness in this matter (blue field in Figure 1b). Kong et al [41] showed that slight changes in the oil color determined by the CIE-Lab method occurred during repeated oil filtration. Referring to the conducted research, it can be concluded that some BEs in small doses (i.e., BE7; 2.5%, Finola CP) do not show the proper adsorption capacity to carotenoid dyes.…”
Section: Resultsmentioning
confidence: 99%